Estimating deformation source parameters using a 3D elastic finite element model including topography and crustal heterogeneity at Askja, Iceland. - Catherine O'Hara 1999- (2023)
Surface deformation is used to investigate subsurface processes at active volcanoes. The use of forward and inverse modeling, by constraining deformation source parameters, can help to improve our understanding of these processes. The last eruption occurred at Askja, Iceland in 1961, followed by inflation 1966-1972 and subsidence since approximately 1973. Askja began uplifting in the summer of 2021, and as of August 2023 is still uplifting. An elastic 3D Finite Element (FE) deformation model was created of Askja incorporating realistic topography and crustal heterogeneity, from seismic tomography, to investigate the inflation signal using the software COMSOL Multiphysics. Topography has a local influence on the predicted deformation signal, particularly around areas of high topographic gradient. Crustal heterogeneity has a more widespread influence, compared to a homogeneous halfspace model, amplifying and slightly narrowing the deformation field. Based on GPS data from Askja during a portion of the inflation period, from September 2021 to September 2022, an inversion using the optimization tool within COMSOL was implemented to estimate latitude, longitude, depth, and pressure change of the deformation source. The inversion using the FE model including topography and crustal heterogeneity produced a best fitting result near the NW edge of lake Öskjuvatn, with a depth of 3.6 km, which is 1 km deeper than found using simple analytical models in a homogeneous halfspace. Advanced FE models allow for the customization of crustal parameters to each volcanic system and improves the understanding of the system, which may be valuable during future periods of unrest. Mælingar á jarðskorpuhreyfingum veita mikilvægar upplýsingar um ýmis ferli í iðrum eldfjalla. Líkanreikningar bæta skilning okkar á þessum ferlum, hvort sem um er að ræða landris eða landsig. Síðasta eldgos í Öskju varð árið 1961. Aflögunarmælingar til eftirlits með Öskjusvæðinu, voru gerðar árlega, 1966-1972 og síðan frá 1983. Fyrstu mælingarnar gáfu til ...